The relationship between premarital sexual knowledge and adolescent sexual behavior at SMA Negeri 1 Nisam - Putri Eliza; Satrinawati Satrinawati; Yuni Sari; Hendrika Wijaya Kartini Putri; Aida Fitriani (Institute Of Computer Science (IOCS), 2026)
Premarital sexual behavior among adolescents has become an urgent public health concern in North Aceh due to increasing reports of risky behaviors and limited access to accurate reproductive health information. The study aimed to determine the relationship between the level of premarital sexual knowledge and sexual behavior among adolescents at SMA Negeris 1 Nisam, North Aceh Regency. This research used a quantitative analytic approach with a cross-sectional design. The population consisted of students of SMA Negeri 1 Nisam, and the sample was selected using proportional random sampling. Data were collected through questionnaires assessing knowledge and sexual behavior and analyzed using the Chi-square test. The results showed that most respondents had a moderate level of premarital sexual knowledge (49.4%) and mild premarital sexual behavior (73%). Statistical analysis revealed a significant relationship between the level of premarital sexual knowledge and adolescent sexual behavior (p-value = 0.003; ? = 0.05). It can be concluded that adolescents with better knowledge of premarital sex tend to exhibit more responsible and less risky sexual behaviors. It is suggested that adolescents should enhance their understanding of reproductive health and sexual education from credible sources to prevent misconceptions and risky behaviors.